MYTHOLOGICAL SYNCRETISM INDUCED BY CONTAC - Gómez Rendón, Jorge (2013)
The present study explores an almost untrodden field in the structuralist mythemic analysis, according to which a myth is a narrative matrix that may and should be read along a diachronic axis. This perspective highlights socio-historical aspects of mythopoesis as mirrored on the matter and pattern of myths. An analytic proposal complementing traditional structuralist analysis is developed through a comparative study of Andoan and other mythologies from the Upper Amazon basin.